Sant Great Wall - Tello, Julio C. (2004)
After several surveys conducted towards the Marañon river, Dr. Julio C. Tello published the results of this research on the Sant Great Wall. Tello stated that this wall was a road that connected the coastal zone with the highlands, and had a religious and economic role. Tello provided a detailed record of the Great Wall course an its branches as well as its adjacent villages, cities and others kinds of building. Finally, he accounted the find of the Ipuna temple dedicated to the Apocatequil god.